Visualization of Henry Manampiring’s Filosofi Teras Book - Amirah, Charissa Myandra; Melini, Ellis; Indrajaya, Ferdinand; Hananto, Brian Alvin (Universitas Multimedia Nusantara, 2025)
Generation Z faces significant emotional challenges, including anxiety, stress, and difficulty regulating emotions—issues worsened by social media pressures. While this generation is highly receptive to visual and digital learning, Henry Manampiring's Filosofi Teras offers valuable Stoic principles like acceptance and self-control, yet its textual format is less engaging for younger audiences. This final project aims to visualize Stoic concepts from the book into an audiovisual narrative format through a web-based video series. The methodology for this project draws on Robin Landa's Five Phases of Graphic Design Process theory combined with Compesi's three-step video production model. The analysis phase utilized Ricoeur’s hermeneutics to understand the meaning of the text through an act of appropriation, which then were used in the Conceptual Design phase. The design outcome consists of five 1–2-minute videos that illustrate the application of Stoic principles in daily life, aligning with the book's text. Although some philosophical considerations were used, the main focus is on the visual design experimentation. This project is expected to offer a more relevant and engaging way to convey Stoic values to Generation Z. Future research could explore developing additional episodes covering other topics within Filosofi Teras or creating audiovisual works based on other philosophical texts. Keywords: Generation Z; Stoicism; Audiovisual narrative; Web series.